Relatório de estágio técnico profissional em medicina veterinária: clínica, cirurgia e odontologia equina - Calza, Tamiris Menin (2023)
The Professional Technical Internship (ETP) is an opportunity to improve and put into practice all the theoretical knowledge acquired during the Veterinary Medicine degree, in the area intended for professional practice. The ETP was carried out in the area of ​​clinic, surgery and equine dentistry, under the academic guidance of Prof. Dr. Maria Isabel Botelho Vieira. The ETP was carried out at the Carolina Zagonel and Eduarda Souza Clinic, from July 17th to November 17th, totaling 700 hours. Through the ETP, it was possible to experience the clinical/surgical and dental routine in the field, helping veterinarians with care, restraint, management of hospitalized patients, imaging exams and procedures. Therefore, this report includes a description of the internship location, the general activities carried out, the conditions monitored during this period and, finally, a case of osteoarthritis and subchondral cyst in a Creole mare will be reported. For me, the supervised professional technical internship was fundamental for both professional and personal development, as I had the opportunity to follow several cases, previously only seen in literature, and have contact with several excellent professionals in the field.